Use of three pins in Gamma Knife stereotactic radiosurgery for brain metastases - Jensen, Garrett L. (J Radiosurg SBRT, 2019)
PURPOSE: We present our institutional experience in treating brain metastases with GK-SRS and a headframe fixed to the skull with only 3 pins to avoid collisions between the headframe and the Gamma Knife (GK) machine. METHODS AND MATERIALS: Among 3500 consecutive patients who received GK-SRS in 2011–2017, 50 had 1 of the 2 anterior pins removed immediately before treatment of ≥1 brain lesion. Endpoints were local control, dosimetric parameters, and toxicity. RESULTS: Median follow-up time for the 49 patients with follow-up was 7.0 months (range 0.2–57.0). Median number of lesions treated per session was 6 (range 1–18); a median 1 lesion was treated with 3-pin fixation (range 1–2) and a median 5 lesions treated with 4-pin fixation (range 0–17) during the same session. Lesions treated with 3-pin fixation were in the occipital lobe (n=41), cerebellum (n=9), or temporal lobe (n=1). No local failures were noted. The sole grade 2 toxicity (partial seizure) was attributed to treatment of a 4-pin-fixed lesion. Except for gradient index, dosimetry did not vary for lesions treated with 3-pin versus 4-pin fixation. CONCLUSIONS: Treating brain metastases with 3-pin fixation did not compromise treatment outcome and is a good option for posterior brain metastases that cannot otherwise be treated with 4-pin GK-SRS.